2010
DOI: 10.1007/s11325-010-0457-x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory events in preterm infants prior to discharge: with and without clinically concerning apnoea

Abstract: Preterm infants with clinically concerning apnoea have similar amounts and types of apnoea but lower oxygen saturation after apnoea compared with controls. The use of oxygen saturation monitoring is more useful than respiratory monitoring alone in recognising these events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…These infants were however immature and relative hypoventilation may have contributed to persistence of atelectasis with resultant ventilation‐perfusion mismatch. We previously reported that preterm infants with clinically concerning apnea are more likely to have CLD than those without symptoms and also have a lower oxygen desaturation in response to events despite the numbers and types of respiratory events being not significantly different to infants without clinical concerning respiratory events …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These infants were however immature and relative hypoventilation may have contributed to persistence of atelectasis with resultant ventilation‐perfusion mismatch. We previously reported that preterm infants with clinically concerning apnea are more likely to have CLD than those without symptoms and also have a lower oxygen desaturation in response to events despite the numbers and types of respiratory events being not significantly different to infants without clinical concerning respiratory events …”
Section: Discussionmentioning
confidence: 93%
“…We previously reported that preterm infants with clinically concerning apnea are more likely to have CLD than those without symptoms and also have a lower oxygen desaturation in response to events despite the numbers and types of respiratory events being not significantly different to infants without clinical concerning respiratory events. 24 A drop of 3% or 4% in oxygen saturation in preterm neonates will be considered benign by many neonatal clinicians especially when occurring from a baseline oxygen saturation of ≥95%.…”
Section: Discussionmentioning
confidence: 99%
“…The AAP recommends that all preterm infants should undergo screening for CR events while in car seats before discharge (21,22), as premature infants are at risk for desaturation and apnea when placed in upright car seats. Moreover, some studies focused on objective methodologies such as 24-h pulse oximetry (23)(24)(25)(26)(27)(28) or polysomnography assessment (24,26,28). However, neither AAP nor CPS specify which should be considered the best technique to objectively assess the CR function and stability before discharging a preterm infant (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Although more than half of the infants were classified as unstable, this cut‐off point was based on our previous work documenting nap polysomnography in preterm infants near discharge. In our previous study, apnoea was defined as a pause of greater than or equal to five seconds . We have previously reported that the median interbreath interval in preterm infants is 1.15 seconds in AS and 1.25 seconds in QS .…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory instability was defined as an obstructive index (OI – total obstructive apnoea per hour) of greater than 10 and/or an apnoea during the study of >20 seconds. This was an arbitrary decision but made because we have previously reported that preterm infants for whom there has been no clinical concern about persistent respiratory events do have up to five obstructive events per hour in AS prior to discharge .…”
Section: Methodsmentioning
confidence: 99%